The Role of State in Regulating Migration: A Study of the Arab Migration to Iraq 632–750 CE - Riaz, Rafia (Islamic Studies, 2012)
The Arab migration to Iraq was a direct consequence of the Arab conquest movement. This migration was provoked by different factors, yet the main motivation was to retain the control of the conquered areas. The migrants moved in the form of a tribal army and after a long journey, during which they kept on settling in different stations, finally settled in the garrison cities of al-K┴fah and al-Ba╖rah. State had played an imperative role in furthering and finalizing the Arab migration to Iraq. The state had comprehended the need to stay at Iraq first in the form of temporary garrisons but finally decided to make it a permanent residence. Migration was a corresponding process of the conquest and the state took decisions about migration along with the changing nature of the conquest. The Arab state was basically motivated for initiating this migration due to military and strategic reasons. Besides, the state was visualizing certain social and economic benefits attached with the process of migration.